2009
DOI: 10.1016/j.jaut.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Environmental triggers of autoimmune thyroiditis

Abstract: Autoimmune thyroiditis is among the most prevalent of all the autoimmunities. Autoimmune thyroiditis is multifactorial with contributions from genetic and environmental factors. Much information has been published about the genetic predisposition to autoimmune thyroiditis both in experimental animals and humans. There is, in contrast, very little data on environmental agents that can serve as the trigger or autoimmunity in a genetically predisposed host. The best-established environmental factor is excess diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 66 publications
5
86
0
16
Order By: Relevance
“…xenobiotics) that can either alter or complex to a defined self or non-self protein, causing a change in its molecular structure that induces an immune response. This fascinating hypothesis has been proposed for numerous autoimmune diseases, particularly based on the observed geoepidemiological gradient [50,120,121] in which definitive confirmation is awaited and should not be considered as exclusive with regard to the role of infectious agents. The hypothesis is supported by a number of epidemiology studies, as previously discussed, as well as by the appearance of autoantibodies in subjects immunized with halothane, an inhalatory anesthetic no longer used, with antibodies crossreacting with lipoylated PDC-E2 [122].…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…xenobiotics) that can either alter or complex to a defined self or non-self protein, causing a change in its molecular structure that induces an immune response. This fascinating hypothesis has been proposed for numerous autoimmune diseases, particularly based on the observed geoepidemiological gradient [50,120,121] in which definitive confirmation is awaited and should not be considered as exclusive with regard to the role of infectious agents. The hypothesis is supported by a number of epidemiology studies, as previously discussed, as well as by the appearance of autoantibodies in subjects immunized with halothane, an inhalatory anesthetic no longer used, with antibodies crossreacting with lipoylated PDC-E2 [122].…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Most of these findings may be reversed after iodine withdrawal (Mizukami et al 1993). In vivo studies showed that while excess iodine is not necessary for the induction of thyroiditis, the ingestion of excess iodine works to exacerbate autoimmune thyroiditis in this genetically predisposed population (Burek and Talor 2009). Clearly, excess iodine intake has many roles in thyroid dysfunction, and one of these roles is to increase thyroglobulin immunogenicity (Papanastasiou et al 2007), while another is to increase adhesion molecules on the thyrocyte itself (Sharma et al 2005;Sharma et al 2008).…”
Section: Disturbs In Iodine-intake Are Closely Related To Thyroid Dismentioning
confidence: 99%
“…7 The exposure to environmental toxicants such as polyaromatic hydrocarbons or polyhalogenated biphenyls, both are commonly used in a variety of industrial applications, have been shown to provoke thyroid autoimmunity not only in experimental animals but also in humans. 8 Several autoimmune disorders have been reported to be associated with autoimmune thyroiditis and may coexist with other organ-specific autoantibodies. 9 Tolerance to self antigen is obtained by elimination of autoreactive T-cells 10 and defect in this mechanism leads to activation of these cells and consequent autoimmunity.…”
Section: Introductionmentioning
confidence: 99%